The critical reception of Flannery O'Connor, 1952-2017 : "searchers and discoverers" - Evans, Robert C., 1955- (Studies in American literature and culture. Literary criticism in perspective., 2018)
The first chronological overview of O'Connor criticism from the publication of her first novel, Wise Blood, in 1952 to the present.